Rancangan Eksperimen-Kuasi - T Dicky Hastjarjo (Faculty of Psychology Universitas Gadjah Mada, 2019)
Many studies in master psychology and professional psychology study programs used quasi-experimental methods, but there was no reference regarding quasi-experiments written in Indonesian. This article will fill in the blanks on reference to quasi-experimental methods. The article explains quasi-experimental design or non-randomized experimental design. According to Campbell quasi experimental design is divided into four types, namely (a) quasi-experimental design without control group or pretest, b) quasi experimental design with control group and pretest, c) time series design, and d) regression discontinuity design. Each type was broken down into a more specific design.